Fenofibrate Therapy in Carnitine Palmitoyl Transferase Type 2 Deficiency - I. Hamilton-Craig; M. Yudi; L. Johnson; R. Jayasinghe (Case Reports in Medicine)
Bezafibrate therapy has been shown to improve beta-oxidation of fatty acids and to reduce episodes of rhabdomyolysis in patients with carnitine palmitoyltransferase type-2 (CPT2) deficiency. We report the efficacy of fenofibrate in a patient with CPT2 deficiency, in whom beta-oxidation was improved but an episode of rhabdomyolysis nevertheless occurred. This suggests additional methods to avoid rhabdomyolysis in patients with CPT2 deficiency should accompany fibrate therapy, including avoidance of muscular overexertion, dehydration, and heat exposure.